Clinical application of whole‐genome low‐coverage next‐generation sequencing to detect and characterize balanced chromosomal translocations. Issue 4 (5th September 2016) - Liang, D.; Wang, Y.; Ji, X.; Hu, H.; Zhang, J.; Meng, L.; Lin, Y.; Ma, D.; Jiang, T.; Jiang, H.; Asan,; Song, L.; et al.
Abstract : Individuals carrying balanced translocations have a high risk of birth defects, recurrent spontaneous abortions and infertility. Thus, the detection and characterization of balanced translocations is important to reveal the genetic background of the carriers and to provide proper genetic counseling. Next‐generation sequencing (NGS), which has great advantages over other methods such as karyotyping and fluorescence in situ hybridization (FISH), has been used to detect disease‐associated breakpoints. Herein, to evaluate the application of this technology to detect balanced translocations in the clinic, we performed a parental study for prenatal cases with unbalanced translocations. Eight candidate families with potential balanced translocations were investigated using two strategies in parallel, low‐coverage whole‐genome sequencing (WGS) followed‐up by Sanger sequencing and G‐banding karyotype coupled with FISH. G‐banding analysis revealed three balanced translocations, and FISH detected two cryptic submicroscopic balanced translocations. Consistently, WGS detected five balanced translocations and mapped all the breakpoints by Sanger sequencing. Analysis of the breakpoints revealed that six genes were disrupted in the four apparently healthy carriers. In summary, our result suggested low‐coverage WGS can detect balanced translocations reliably and can map breakpoints precisely compared with conventional procedures. WGS may replace cytogenetic methods in the diagnosis of balanced translocation carriers in the clinic. Abstract :